PENERAPAN TERAPI BEKAM KERING DALAM MENURUNKAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI WILAYAH BINAAN PUSKESMAS ROWOSARI SEMARANG: APPLICATION OF DRY CUPPING THERAPY IN REDUCING BLOOD PRESSURE IN THE ELDERLY WITH HYPERTENSION IN AREA PUSKESMAS ROWOSARI SEMARANG - Dita Amalia Lutfiana; Margiyati Margiyati (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2021)
Elderly is a population at high risk of experiencing hypertension due to the aging process. The treatment of hypertension in the elderly is not effective yet, because it only reduces hypertension by 8%, the disease often recurs and requires a long process. Dry cupping therapy is one of the non-pharmacological therapies that are safe and fast through the skin suctioning techniques to reduce blood pressure in the elderly. This study aims to determine the description of the application of dry cupping therapy in reducing blood pressure in the elderly with hypertension in the Rowosari Community Health Center Semarang. This type of research is descriptive research with a case study approach. Subjects used were 2 respondents with criteria of age > 60 years, had first-degree hypertension, and were able to self-care. Blood pressure measurement using a sphygmomanometer. Dry cupping therapy interventions carried out for ± 15-30 minutes once a day. The results of data analysis showed that subject I decreased blood pressure from 150/90 mmHg to 140/90 mmHg and subject II decreased blood pressure from 150/90 mmHg to 140/80 mmHg. The conclusion of this study is dry cupping therapy influences in reducing blood pressure in the elderly with hypertension and is recommended as a nursing intervention in the management of blood pressure in the elderly with hypertension.